Endobronchial lipoma; A rare case report - Koc, Mustafa (My University, 2020)
The endobronchial lipoma is a rare benign tumor that can cause lung injury. It constitutes 0.1% of all lung tumors. Endobronchiallipoma can be confused clinically with malignant tumors. A 45-year-old female with a history of previous limb malignant neoplasmapplied to the emergency room with complaints of shortness of breath, chest pain. Upon detecting atelectasis in the left lunglower lobe, thorax computed tomography (CT) was performed for further examination and evaluation, and then PET CT examinationwas performed in thorax CT, it was observed that there was a non-contrasted, smooth solid mass that contained the fatty values,occluding the left lung lower lobe bronchus and atelectasis in the lower lobe of the lung. It was removed totally with bronchoscopy.The histopathological examination of the mass was reported as an endobronchial lipoma. We decided to present this rare case withradiological imaging findings.
Keywords: Genel ve Dahili Tıp